DIRECTNESS AND INDIRECTNESS IN THE ANGLICIST AND THE VIETNAMESE TEACHERS’ ORAL FEEDBACK ON THEIR STUDENTS’ SPEAKING PERFORMANCES = Tính trực tiếp và gián tiếp trong lời nhận xét của giáo viên nước ngoài và giáo viên Việt Nam đối với phần trình bày của sinh viên trong luyện tập kĩ năng nói tiếng Anh - Phạm, Thị Thu Thảo (2020)
As one of the most significant dimensions in cross-cultural communication, directness and indirectness are claimed to have a strong connection with speech act performance in communication. That evokes many studies into the directness and indirectness in different aspects of reality communication. This study was conducted with the aims to provide a view in the use of directness and indirectness expressed through teachers’ oral feedback for their students in language classroom communication. The data were collected from three Anglicist teachers and three Vietnamese teachers by recording their oral feedback on students’ speaking performances. The collected data then are analyzed by qualitative methods. Based on the collected data, some results have been found out. Firstly, the extent of directness in the Anglicist teachers’ feedback and the Vietnamese teachers’ feedback is different. Though the use of strategies are somehow balanced, the Vietnamese teachers appear to be more indirect due to the frequent use of linguistic devices in their feedback. It also reveal that the number of strategies as well as the modifiers are the factors which contribute to the identification of degree of direness in teachers’ oral feedback. Secondly, the use as well as the choices of strategies and modifiers of the Anglicist teachers and the Vietnamese teachers are put in comparison to figure out the similarities and differences.